Association of Xerostomia with Diabetes a Cross Sectional Study in Subset of Karachi: Xerostomia and Diabetes - Arfeen, Nizam Ul; Haider, Ambreen Khurshid; Phull, Ghulam Muhammad; Rathore, Padma; Ahmed, Syed Zaryab (Pakistan Journal of Health Sciences, 2025)
Xerostomia, is a common oral symptom of Diabetic Mellitus (DM). It has a detrimental impact on clinical procedures and outcomes due to decreased saliva. Considering its impact on oral cavity and dental procedures it is important to identify the Association of xerostomia with diabetes. Objective: To identify the prevalence and association of xerostomia in diabetic patients subset of Karachi. Methods: It was a cross sectional study conducted from January 2024 to October 2024. The calculated sample size was 63 which was increased to 75. Patients reporting to OPD with history of diabetes were recruited and they were advised to get their HbA1c and random blood sugar level (RBS) checked. After getting their HbA1c and RBS reports their stimulated salivary flow rate was calculated. Stimulated salivary flow less than 0.7ml/min was considered as low. Chi square and independent t-test was applied for comparison at 95% confidence interval and p value less than 0.05 was considered as significant. Results: The xerostomia was found to be present in 47 (62.66%) participants.The salivary flow was identified as 0.46 ± 0.31 in diabetic patients with xerostomia, compared to female, male diabetic patients had less salivary flow at 7.01 ± 0.62 HbA1c and 220.53 ± 5.12 RBS. Conclusions: There was 62.66% prevalence in diabetic patients in the recruited subset of Karachi. Males had more prevalence than females. Higher HbA1c and RBS levels were associated with the presence of xerostomia.